Costs of dengue control activities and hospitalizations in the public health sector during an epidemic year in Urban Sri Lanka - Thalagala, Neil; Tissera, Hasitha; Palihawadana, Paba; Amarasinghe, Ananda; Ambagahawita, Anuradha; Wilder-Smith, Annelies; Shepard, Donald S.; Tozan, Yeşim (PLoS neglected tropical diseases, 2016)
Background Reported as a public health problem since the 1960s in Sri Lanka, dengue has become a high priority disease for public health authorities. The Ministry of Health is responsible for controlling dengue and other disease outbreaks and associated health care. The involvement of large numbers of public health staff in dengue control activities year-round and the provision of free medical care to dengue patients at secondary care hospitals place a formidable financial burden on the public health sector. Methods We estimated the public sector costs of dengue control activities and the direct costs of hospitalizations in Colombo, the most heavily urbanized district in Sri Lanka, during the epidemic year of 2012 from the Ministry of Health’s perspective. The financial costs borne by public health agencies and hospitals are collected using cost extraction tools designed specifically for the study and analysed retrospectively using a combination of activity-based and gross costing approaches. Results The total cost of dengue control and reported hospitalizations was estimated at US$3.45 million (US$1.50 per capita) in Colombo district in 2012. Personnel costs accounted for the largest shares of the total costs of dengue control activities (79%) and hospitalizations (46%). The results indicated a per capita cost of US$0.42 for dengue control activities. The average costs per hospitalization ranged between US$216-609 for pediatric cases and between US$196-866 for adult cases according to disease severity and treatment setting. Conclusions This analysis is a first attempt to assess the economic burden of dengue response in the public health sector in Sri Lanka. Country-specific evidence is needed for setting public health priorities and deciding about the deployment of existing or new technologies. Our results suggest that dengue poses a major economic burden on the public health sector in Sri Lanka.